Perancangan sistem kriptografi dengan metode advanced encryption standard (AES) berbasis web - Tulus Marbun (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Digital information protection has become a primary concern for modern security institutions, particularly units responsible for managing classified documents and cyber investigations.To develop a web-based cryptographic application implementing Advanced Encryption Standard for securing digital files.This study employs a waterfall system development lifecycle encompassing requirement analysis, architectural design, coding, and evaluation phases. The platform was constructed using modern JavaScript technologies integrating AES-256 GCM mode encryption and PBKDF2 key derivation functions to strengthen password-based authentication mechanisms.The application successfully executes encryption-decryption processes adhering to international security standards. The platform supports multi-format file processing without capacity limitations, featuring an intuitive interface with drag-drop functionality. Security evaluation demonstrates resilience against brute-force attacks through implementation of 100,000 PBKDF2 iterations and 128-bit salt randomization.The constructed web cryptographic platform effectively enhances digital asset protection through robust encryption standard implementation and practical interface design. This research opens opportunities for exploring post-quantum cryptographic algorithms as anticipation for future computational threats, integrating digital signature mechanisms for document authenticity verification, constructing comprehensive activity logging systems, implementing layered encryption for highest data classification levels,